SIMULASI PENERAPAN TEKNOLOGI FACE RECOGNITION PADA APLIKASI PENDATAAN KEHADIRAN KARYAWAN / KARYAWATI TERINTEGRASI E-MON SISTEM PENGGAJIAN DENGAN PENDEKATAN EIGENFACE DAN UXD LARAVEL VERSI 5.6 BERBASIS CLOUD SERVICE - Raditya Rimbawan; Suharyanti Suharyanti; Amat Basri (Jurnal Pepadun, 2021)
Abstract — Face recognition is a face-oriented recognition method by comparing patterns that have previously been stored in the database. In general, facial image recognition systems are divided into two types, namely feature based systems and image based systems. To carry out facial image recognition, there are several kinds of approach algorithms that can support the processing of the face image. One approach algorithm that is well known and capable of processing images with a good level of accuracy is the eigenface approach. By using the eigenface approach, the face image will be processed by performing a matrix calculation, which results in an eucludian distance to be able to get the suitability of the face image. so this research produces a result which includes: the results of the test on the FGD Functional says for the accepted percentage is: 73% for not accepted is 27%, for Non-Functional FGD says for the accepted percentage is 82% and not accepted is 18 %, and for the results of testing the adaptation of ISO 9126 in the good category with a percentage result of 79%, and the last test result, namely the Blackbox Testing test to be accepted is 83% and for the results the percentage that is not accepted is 17%